2011
DOI: 10.3177/jnsv.57.162
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Induction of SI and SGLT1 Genes in Rats by High-Starch/Low-Fat Diet Is Associated with Histone Acetylation and Binding of GCN5 on the Genes

Abstract: SummaryThe intestinal expression of genes involved in carbohydrate digestion and absorption, such as sucrase-isomaltase (SI) and sodium-dependent glucose cotransporter (SGLT1), is higher in rodents fed a high-starch/low-fat (HS) diet than in those fed a lowstarch/high-fat (LS) diet. In the present study, we investigated whether the HS diet-induced induction of SI and SGLT1 in the rat jejunum is coordinately regulated by nuclear transcription factors, histone acetylation, or histone acetyltransferases. HS diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…5) Recent studies from this laboratory have demonstrated that the induction of SGLT1 and GLUT5 genes by feeding a high-carbohydrate diet is associated with acetylation of histone H3 and H4 around these genes, in particular on transcribed region of the genes. 6,7) Histone acetylation, one of the epigenetic memories written on the chromatin, contributes to gene activation by modulating chromatin structure and recruiting coactivator proteins. 8) In particular, histone H3 acetylation is important for the transcriptional regulation because the acetylation of the histone H3 starts to transcription.…”
mentioning
confidence: 99%
“…5) Recent studies from this laboratory have demonstrated that the induction of SGLT1 and GLUT5 genes by feeding a high-carbohydrate diet is associated with acetylation of histone H3 and H4 around these genes, in particular on transcribed region of the genes. 6,7) Histone acetylation, one of the epigenetic memories written on the chromatin, contributes to gene activation by modulating chromatin structure and recruiting coactivator proteins. 8) In particular, histone H3 acetylation is important for the transcriptional regulation because the acetylation of the histone H3 starts to transcription.…”
mentioning
confidence: 99%
“…8) We had demonstrated in our previous study that a high-carbohydrate diet induced the binding of GCN5 to acetylated histones around the genes encoding sucrase-isomaltase, which participates in sucrose digestion in the small intestine, and Slc5a1, which encodes a glucose and galactose transporter in the small intestine. 21) In addition, we have reported that the binding of CBP to acetylated histones around the maltase-glucoamylase gene, which participates in starch digestion in the small intestine, and its expression in the jejunum of mice were enhanced by a high-carbohydrate diet. 22) These HATs, particularly GCN5 and CBP, may therefore be related to the induction of the Slc2a5 gene by fructose forcefeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that histone acetylation around the rat SI gene was lower in the distal transcribed region and out of gene than in the promoter/enhancer and proximal transcribed regions. 21) Recent studies have demonstrated that histone acetylation in the promoter/ enhancer region was necessary for the transcription initiation step, while that in the proximal transcribed region was necessary for the transcription elongation step. 25,26) These results indicate that histone acetylation in the promoter/enhancer and proximal transcribed regions would be necessary for inducing the Slc2a5 gene by force-feeding fructose.…”
Section: Discussionmentioning
confidence: 99%
“…This is subsequently bound by positive elongation factor b (P-TEFb), which is a cyclin T1-CDK9 complex. BRD4 and the associated P-TEFb complex on the gene body region enhance transcriptional elongation by phosphorylating RNA polymerase II at the second serine residue of the C-terminal domain [12][13][14] (Figure 5B). …”
Section: Epigenetic Responses To Environmental Factorsmentioning
confidence: 99%
“…The epigenetic model of gene regulation based on histone modifications and DNA methylation in the gene body region explains the efficacy of mRNA synthesis. Our recent studies in rats have demonstrated that carbohydrate intake increases histone acetylation in the gene body region, rather than in the promoter/enhancer region, of carbohydrate metabolism-related genes, such as sucrose-isomaltase, sodium glucose transporter 1, and glucose transporter 5 in the small intestine [12,13], and fatty acid synthase in the liver during the suckling-weaning transition period [14]. In addition, we have demonstrated that fructose-inducible genes related to fat accumulation, such as Cyp8b1, Dak, and Plin5, are regulated by BRD4 in the liver [15].…”
Section: Epigenetic Responses To Environmental Factorsmentioning
confidence: 99%